Precision nutrient management for enhanced yield and profitability of maize (Zea mays) - Singh, A K; Jat, S L; Parihar, C M; Kumar, Mahesh; Singh, C S; Hallikeri, S S; Sreelatha, D; Manjulatha, G; Mahala, D M (The Indian Journal of Agricultural Sciences, 2020)
A three-year study was carried out at six locations in three agro-ecologies representing the areas of irrigation water availability at critical stages during kharif maize (Zea mays L.) in North Western Plain Zone (NWPZ), North Eastern Plain Zone (NEPZ) and Peninsular Zone (PZ) for optimizing the nutrient requirement and realizing potential yield of the popular genotypes. The study included five popular genotypes/hybrids with three nutrient management practices of RDF, 50% RDF/Farmer Fertilizer Practices (FFP) and nutrient expert based site-specific nutrient management (NE-SSNM) in the split-plot design and replicated thrice. The grain yield of maize was significantly higher at four locations with NE-SSNM however; it was at par with RDF at two locations. The gross returns followed the same trend as of grain yield but the returns over fertilizer cost (ROFC) were significantly higher with NE-SSNM which indicates that the use of these nutrient management practices has the potential to rationalize the nutrient management practices in maize. Hence, it was concluded that the NE-SSNM could be an effective strategy for realizing the potential yield and enhancing net returns of maize production in NWPZ, NEPZ and PZ.